Lowering cholesterol, blood pressure, or both to prevent cardiovascular events: results of 8.7 years of follow-up of Heart Outcomes Evaluation Prevention (HOPE)-3 study participants. (8th May 2021) - Bosch, Jackie; Lonn, Eva M; Jung, Hyejung; Zhu, Jun; Liu, Lisheng; Lopez-Jaramillo, Patricio; Pais, Prem; Xavier, Denis; Diaz, Rafael; Dagenais, Gilles; Dans, Antonio; Avezum, Alvaro; et al.
Abstract: Aims: Rosuvastatin (10 mg per day) compared with placebo reduced major adverse cardiovascular (CV) events by 24% in 12 705 participants at intermediate CV risk after 5.6 years. There was no benefit of blood pressure (BP) lowering treatment in the overall group, but a reduction in events in the third of participants with elevated systolic BP. After cessation of all the trial medications, we examined whether the benefits observed during the active treatment phase were sustained, enhanced, or attenuated. Methods and results: After the randomized treatment period (5.6 years), participants were invited to participate in 3.1 further years of observation (total 8.7 years). The first co-primary outcome for the entire length of follow-up was the composite of myocardial infarction, stroke, or CV death [major adverse cardiovascular event (MACE)-1], and the second was MACE-1 plus resuscitated cardiac arrest, heart failure, or coronary revascularization (MACE-2). In total, 9326 (78%) of 11 994 surviving Heart Outcomes Prevention Evaluation (HOPE)-3 subjects consented to participate in extended follow-up. During 3.1 years of post-trial observation (total follow-up of 8.7 years), participants originally randomized to rosuvastatin compared with placebo had a 20% additional reduction in MACE-1 [95% confidence interval (CI), 0.64–0.99] and a 17% additional reduction in MACE-2 (95% CI 0.68–1.01). Therefore, over the 8.7 years of follow-up, there was a 21% reduction in MACE-1 (95% CI 0.69–0.90, P = 0.005) and 21% reduction in MACE-2 (95% CI 0.69–0.89, P = 0.002). There was no benefit of BP lowering in the overall study either during the active or post-trial observation period, however, a 24% reduction in MACE-1 was observed over 8.7 years. Conclusion: The CV benefits of rosuvastatin, and BP lowering in those with elevated systolic BP, compared with placebo continue to accrue for at least 3 years after cessation of randomized treatment in individuals without cardiovascular disease indicating a legacy effect. Trial Registration Number: NCT00468923 Graphical Abstract: